Development and efficacy of an online wheelchair maintenance training program for wheelchair personnel. Issue 1 (2nd January 2021) - Múnera, Sara; Pearlman, Jon; Toro, Maria; Worobey, Lynn; Boninger, Michael; Cooper, Rory A
ABSTRACT: Objectives: To develop an online version of the wheelchair maintenance training program (WMTP) and compare learning outcomes from the in-person and online programs using the wheelchair maintenance training questionnaire (WMT-Q), administered before and after the intervention. Design: Iterative development of an online version of the WMTP and implementation. Setting: Online. Participants: 26 graduate and undergraduate students. Intervention: Web-based training. These results are compared with those from another study of the in-person WMTP with 10 participants. Main outcome measures: Feedback survey and WMT-Q. Results: The training program was well-received and valued by all 26 participants. A significant increase in all scores after the online training program was found, based on pre-/post-intervention scores. In manual wheelchair open-ended questions, knowledge increased from 16% to 21%, p < .05; in power wheelchair open-ended questions, from 9% to 31%, p < .05; in multiple-choice questions related to knowledge, from 27% to 59%, p < .05; confidence increased from 8% to 80%, p < .05; and capacity from 12% to 88%, p < .05. There was no statistical difference in WMT-Q scores between individuals who participated in the in-person and online programs. Conclusion: This study indicates that there was a similar-increased knowledge for participants, indicating that web-based training may be a viable approach for delivering maintenance training.